Comparison of RNA content from hydrophobic interaction chromatography‐isolated seminal plasma exosomes from intrauterine insemination (IUI) pregnancies. (27th November 2021) - Lal, Arnav; Pike, James Frederick W.; Polley, Emily L.; Huang, Sisi; Sanni, Mustapha; Hailat, Tareq; Zimmerman, Shawn; Clay‐Gilmour, Alyssa; Bruce, Terri F.; Marcus, Kenneth R.; Roudebush, William E.; Chosed, Renee J.
Abstract: Male factors account for roughly half of infertility cases, with most male infertility diagnosed as idiopathic. Researchers predicting intrauterine insemination success rates have identified multiple prognostic factors, including semen parameters and seminal fluid composition. Seminal plasma contains extracellular exosomes, which contain RNAs and proteins involved in spermatogenesis. The contents of seminal plasma exosomes may be an indicator of overall sperm quality or fertility potential; therefore, analysis of exosomes may provide a measure for sperm viability and fertilization potential. In our study, exosomes were isolated and purified from seminal plasma obtained from IUI treatments with known pregnancy outcomes. We used a unique method to isolate the exosomes which made use of the hydrophobic interaction chromatography method. RNASeq was performed on RNAs from the purified exosomes. This analysis revealed holistic trends, including increased expression associated with RNA originating from chromosomes 1, 10, 12, 16 and 21. Overall, total RNA was significantly decreased and rRNA was significantly increased in successful IUI attempts. Furthermore, we found specific mRNAs and lincRNAs associated with positive versus negative pregnancy outcomes. Our study isolated and purified seminal plasma exosomes without ultracentrifugation, and it provides further evidence for differences in seminal plasma exosome molecular contents associated with pregnancy status.